(untitled) (Revista de Ciências Agroveterinárias, 2005)
The soil-borne wheat mosaic disease (SBWMD) significantly impacts wheat crops. In Brazil, this disease is caused by the wheat stripe mosaic virus (WhSMV). Typical symptoms of SBWMD were observed in a commercial wheat field in Campos Novos, Santa Catarina, Brazil. This study aimed to elucidate the etiological agent of SBWMD in wheat crop in the state of Santa Catarina. Total RNA was extracted from symptomatic sample using TRIzol, following subsequent RT-PCR. Specific primer pairs were used to amplify genomic regions of 641 bp and 872 bp, corresponding to the coat protein (CP) and partial replicase genes, respectively. Amplicons were sequenced and the resulting nucleotide sequences were compared with WhSMV sequences from GenBank using a BLASTn search. The SDT program was used to determine nucleotide identity, and phylogenetic relationships were established using the MEGA11 software. Analyses were performed on a global dataset that included sequences obtained in this study and sequences previously characterized in South Africa, Paraguay and Brazil. The nucleotide sequences showed an identity ranging from 94% to 100% for the two analyzed regions when subjected to paired analysis. Based on specific primers amplification and aminoacid sequence of CP identity higher than 90% when compared to other isolates, the viral isolate characterized in this study is WhSMV. Phylogenetic analyses revealed two distinct clades. Notably no demarcation was observed between the WhSMV isolate characterized in this study and Brazilian isolates previously characterized, indicating a close relationship between them. This is the first report of WhSMV associated with wheat mosaic disease in Santa Catarina, Brazil.